miR-133b suppresses metastasis by targeting HOXA9 in human colorectal cancer - Wang, Xiao (Oncotarget, 2017)
Functions and mechanisms of microRNA (miRNA) involved in colorectal cancer (CRC) metastasis are largely unknown. Here, a miRNA microarray analysis was performed in CRC primary tissues and metastatic hepatic tissues to disclose crucial miRNA involved in CRC metastasis. MiR-133b was decreased and negatively correlated with metastasis in CRC. Overexpression of miR-133b significantly suppressed metastasis of CRC in vitro and in vivo. HOXA9 was identified as a direct and functional target of miR-133b. In addition, HOXA9 was negatively correlated with miR-133b and promoted CRC malignant progress. Moreover, miR-133b decreased HOXA9 expression, and subsequently downregulated ZEB1 and upregulated E-cadherin expression. Intriguingly, lower miR-133b and higher HOXA9 expression significantly contributed to poorer outcomes in CRC patients. Multivariate analysis indicated that miR-133b was an independent and significant predictor of CRC patient overall survival. In conclusion, we newly determined that miR-133b targeted the HOXA9/ZEB1 pathway to promote tumor metastasis in CRC cells. This axis provided insights into the mechanism underlying miRNA regulation of CRC metastasis and a novel therapeutic target for CRC treatment.